CASPASE-3 AKTIF DI LEUKEMIA MIELOSITIK AKUT (LMA) DAN LEUKEMIA LIMFOBLASTIK AKUT (LLA) - Agus Setiawan; Indarini Indarini; Lyana Setiawan; Siti Boedina Kresno; Nugroho Prayogo; Arini Setiawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Dysregulation of apoptosis plays an essential role either in leukemogenesis or treatment response. Caspase-3 is a cysteine protease that functions as the final common mediator of apoptosis. The expression of the active caspase-3 is presumed as a predictor of prognosis and is able to predict the chemotherapy sensitivity. The aim of this study is to identify and to know the profile of active caspase-3 in Acute Myeloid Leukaemia (AML) and Acute Lymphoblastic Leukaemia (ALL), to correlate its expression in marrow and peripheral blood mononuclear cells, and to verify the extent of its use as a complete remission predictor after induction treatment. The study subjects consisted of patients who were diagnosed as AML and ALL with marrow and peripheral blood examination performed at the Department of Clinical Pathology Dharmais Cancer Hospital and CiptoMangunkusumo Hospital. Based on this study, it is revealed that the active caspase-3 expression in mononuclear marrow cells was higher in AML compared to ALL (p=0.033), active caspase-3 expression in marrow showed a strong correlation (r=0.764; p=0.001) to peripheral blood mononuclear cells in ALL and a medium correlation (r=0.594; p=0.042) in AML. The expression of the active caspase-3 in ALL patients was lower in complete remission patients compared to the non-complete remission patients. Regarding to this study it is recommended to measure the active caspase-3 along with molecules integrating in apoptosis signaling pathways such as cytochrome-c and in the formation of apoptosome.